Out of School and Out of Work : A Conceptual Framework for Investigating 'ninis' in Latin America and the Caribbean - Behrman, Jere R.; de Hoyos, Rafael; Székely, Miguel (World Bank, Washington, DC, 2016)
The proportion of youth that is not in work or in school or ninis1 in Latin America and the Caribbean (LAC) remains high. The latest estimates show that about 19 per cent of 15-24 years olds in the region, were in this status in 2010 (de Hoyos, Rogers and Popova (2013). This status entails a series of negative implications for the life-cycle development of the youth involved with a break in the human capital accumulation process that translates into a reduction in future productivity and labor market outcomes. A large share of ninis might also entail risks for society at large through potential short-term effects such as crime rates, and through the long-term sequels from not fully capitalizing on the ‘demographic window of opportunity’ of historically low economic dependency ratios, among others. The objective of this paper is to develop a conceptual framework for laying out the main elements involved in the dynamics of choices and restrictions faced by youth in the 15-24 age range. The paper also discusses different approaches that could be used to test the empirical validity of the theoretical implications presented here. The paper includes four sections. Section two starts with a simple characterization of the life-cycle transition of time uses for youth in LAC. Section three introduces a more formal presentation of what underlies these processes and what impact they may have. Section four addresses the considerations for empirical analyses and policy discussion. The last section includes some final remarks.